The influence of strength training on taekwondo athletes' reaction speed - He, B.; Wan, Y. (Revista Brasileira de Medicina do Esporte, 2022)
Introduction: Taekwondo is a skill-oriented confrontational event. Athletes` physical fitness and flexible changes in skills and tactics have become the cornerstone of athletes` victory. Objective: The objective was to explore the influence of strength training on the reaction speed of boxing athletes. Method: 8 master-class Taekwondo athletes, 16 first-class Taekwondo athletes, and 30 second-class Taekwondo athletes from a particular province were selected as Group A, B, and C. The control groups were Group A1, B1, and C1. Results: Group B athletes showed significant changes in 15s front kick and 15s high leg lift. Group C athletes showed highly significant differences in rapid strength. After the traditional fast strength training in the control group, all the Group C1 had significant changes in the test. However, Group B1 athletes only had substantial changes in 15s down split and 15s front kick. There was no significant change in all indexes of Group A1 athletes before and after the experiment. Conclusion: The analysis of experimental data shows that core strength training significantly improves the reaction speed of Taekwondo athletes.